2007
DOI: 10.1038/sj.onc.1210297
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation and transcriptional downregulation of the CITED4 gene at 1p34.2 in oligodendroglial tumours with allelic losses on 1p and 19q

Abstract: Deletions of chromosomal arms 1p and 19q are frequent in oligodendroglial tumours and have been associated with sensitivity to radio-and chemotherapy as well as favourable prognosis. By using microarray-based expression profiling, we found that oligodendroglial tumours with 1p and 19q losses showed significantly lower expression of the CBP/p300-interacting transactivator with glutamic acid/aspartic acid-rich carboxyl-terminal domain 4 gene (CITED4) at 1p34.2 as compared to tumours without 1p and 19q losses. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 23 publications
2
29
1
Order By: Relevance
“…Thereby, we identified a set of candidate genes showing significantly reduced mRNA expression levels in 1p/19q-deleted as compared with 1p/19q-intact tumours (Tews et al, 2006). These included the CITED4 gene at 1p34.2 (Tews et al, 2007) as well as several other genes, among which the peroxiredoxin 1 (PRDX1) gene appeared as a particular promising candidate because (i) it was independently identified in a proteomic screen of lowgrade oligodendroglial tumours (Grzendowski et al, 2010), (ii) was reported to have tumour-preventive functions (Neumann et al, 2003) and (iii) was linked to radiotherapy response of cancer cells Zhang et al, 2008). Here, we report on the mechanism leading to the frequent downregulation of PRDX1 mRNA and proteins in 1p/19q-deleted gliomas and provide first evidence for a role of peroxiredoxin 1 in the response of Hs683 glioma cells to TMZ and ionizing irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, we identified a set of candidate genes showing significantly reduced mRNA expression levels in 1p/19q-deleted as compared with 1p/19q-intact tumours (Tews et al, 2006). These included the CITED4 gene at 1p34.2 (Tews et al, 2007) as well as several other genes, among which the peroxiredoxin 1 (PRDX1) gene appeared as a particular promising candidate because (i) it was independently identified in a proteomic screen of lowgrade oligodendroglial tumours (Grzendowski et al, 2010), (ii) was reported to have tumour-preventive functions (Neumann et al, 2003) and (iii) was linked to radiotherapy response of cancer cells Zhang et al, 2008). Here, we report on the mechanism leading to the frequent downregulation of PRDX1 mRNA and proteins in 1p/19q-deleted gliomas and provide first evidence for a role of peroxiredoxin 1 in the response of Hs683 glioma cells to TMZ and ionizing irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…MS-HRM primers were designed in the region to match the region that was previously reported to be methylated for CITED4 by Tews et al [13]. The MS-HRM primers were CITED4-F 5 0 -GGGGAAGTTTCGTTTTT GGGTATAAG-3 0 and CITED4-R 5 0 -ACCGCAACCT AAAATCACAAAAACC-3 0 .…”
Section: Dna Sequencingmentioning
confidence: 99%
“…This could be significant because Cited4 is epigenetically regulated whereby hypermethylation of its CpG island causes lower expression. 244 Our results are in line with the general consensus showing that altered metabolism regulates the epigenetic landscape. [321][322][323] While additional work establishing the mechanistic link between metabolism and epigenetics is required, our results provide new insights into the regulation of gene expression via metabolism.…”
Section: Periodic Decreases In Myocardial Glycolysis Activate the Carsupporting
confidence: 80%
“…244 While our data do not address this mechanism, they suggest that low glycolytic rates could prevent such methylation events, thereby permitting Cited4 transcription, especially when appropriate stimuli are present.…”
Section: Discussionmentioning
confidence: 82%